The Adoption Level of Enterprise Resource Planning System (ERP) and its Effect in Achieving the Quality of Accounting Information System (AIS) In the Jordanian Industrial Sector: The Perception of Internal Stakeholders - Salman, Khadejah; Bani-Khalid, Tareq (The Arab Journal of Administration, 2020)
This study aimed to identify the views of stakeholders on the level of adoption of the Enterprise Resource Planning (ERP) system and its impact on the Quality of Accounting Information System (QAIS) in Jordanian industrial companies. The sample of this study included the following internal stakeholder groups (i.e.: financial managers, heads of accounting departments, accountants, and employees in IT departments of industrial companies). Analytical descriptive tests adopted in this study to determine the degree of adoption of ERP systems in the sampled companies. Multiple linear regression models were also the most appropriate analysis technique to analyse possible relationships between sub-independent variables on the dependent variable. The study reached a set of results, most notably: as the stakeholders’ perceptions that adoption of ERP systems came at a high degree. The results also showed that there is a statistically significant effect of adoption of supply management system on the quality of accounting information systems, while the inventory management systems, human resources and financial resources did not have a statistically significant impact on the dependent variable. Accordingly, it’s recommended that top management should continue their support to the procedures of the supply chain system to improve the quality of accounting information systems. Furthermore, the study also recommended that there is urgent need to understand more about the perceptions of other groups of stakeholder on the practices of inventory management and human resource management. Understanding all the surrounding factors as an attempt to understand the challenges of ERP adoption was also from our important recommendations in order to support the quality of accounting information system.